Metallic Nanoparticle‐Enabled Sensing of a Drug‐of‐Abuse: An Attempt at Forensic Application. (19th May 2020) - Hu, Ming; Han, Qinyu; Xing, Bengang
Abstract: γ‐Hydroxybutyric acid (GHB) functions as a depressant on the central nerve system and serves as a pharmaceutical agent in the treatment of narcolepsy and alcohol withdraw. In recent years, GHB has been misused as a recreational drug due to its ability to induce euphoric feelings. Moreover, it has gained increasing attention as a popular drug of abuse that is frequently related to drug‐facilitated sexual assaults. At the moment, detection methods based on chromatography exhibit extraordinary sensitivity for GHB sensing. However, such techniques require complicated sample treatment prior to analysis. Optical sensors provide an alternative approach for rapid and simple analysis of GHB samples. Unfortunately, currently reported probes are mostly based on hydrogen bonding to recognize GHB, and this raises concerns about, for example, the lack of specificity. In this work, we report a bioinspired strategy for selective sensing of GHB. The method is based on specific enzyme recognition to allow highly selective detection of GHB with minimum interference, even in a complex sample matrix (e. g., simulated urine). In addition, the result can be obtained by either quantitative spectroscopy analysis or colorimetric change observed by the naked‐eye, thus demonstrating its potential application in drug screening and forensic analysis. Abstract : GHB analysis in forensic sample matrices : The date‐rape drug γ‐hydroxybutyric acid (GHB) can be detected after a highly specific enzymatic reaction that generates NADH. NADH helps to reduce gold(III) species to form pinkish AuNPs that can be seen even with the naked eye in a variety of spiked drinks. The strategy can also be used to analyze GHB in complicated biological samples.